The Role of Digital Literacy in Developing the Teaching Creativity of Elementary School Teachers - Zaini, Muhammad; Aqodiah, Aqodiah; Astini, Baiq Ida (Department of Physics Education, Universitas Mataram, 2025)
This research investigates how digital literacy contributes to enhancing teachers' creativity in elementary school learning activities. Employing a qualitative approach with a case study design, the study was conducted at SDN 1 Kekait. Participants included four classroom teachers from grades IV and V, the school principal, and students from classes IV A, IV B, V A, and V B, all selected purposively due to their active engagement in technology-integrated learning. Data were gathered through observations, semi-structured interviews, and document analysis, and interpreted using the Miles and Huberman interactive model. The findings indicate that teachers with higher levels of digital literacy are better equipped to design innovative teaching materials, foster student motivation, and promote active classroom participation, leading to more engaging and interactive learning environments. Nevertheless, the study identified several challenges, including inadequate infrastructure, disparities in teachers' technological competencies, and insufficient ongoing digital literacy training. These results underscore the need for comprehensive, inclusive, and adaptive strategies to strengthen digital literacy as a means to advance teacher creativity and elevate the overall quality of primary education.